The development of care of single mothers in Poland: Single Mothers’ Houses as an example of institutional care - Bajcarczyk, Renata; Florek, Renata; Kozieł, Dorota (Medical Studies/Studia Medyczne, 2021)
In every culture, ethnic group, or society, there have been women who raise their offspring alone. Throughout the centuries, lonely motherhood has been considered as a disgrace for the woman and for her family. Even rich women were exposed to social ostracism and condemnation, and their children were named ‘bastard’. The women found care and help only from the churches and from rich philanthropists. Institutional help from the state began only at the beginning of the 20th century. Today, through to the social and moral changes of the last dozen years, single motherhood has started to be transformed into self-reliant motherhood. Thanks to the help of the state, single women can cope with the situation much better than their precursors. There is still a group of single mothers who, on account of their bad economic situation, family violence, or life incapability, need special care and support.